The Political Right in Italy: The Rise of Conservative Currents and Their Impact on Public Policy-making (قضايا سياسية, 2025)
Apart from the historical roots of the political work of right-wing parties in Italian political life, the general political conditions of the last century led to the rise of totalitarian fascism in Italy This study begins by shedding light on the rise of the right-wing movement in Italy during the twenty-first century, which was represented by the rise of conservative parties to power in a manner that reflected the shift in political and popular positions on various issues, most notably immigration, the economy, cultural identity, and foreign relations, particularly with the European Union and the United States The study concludes that the rise of the Italian right reflects a structural shift in the country's political and societal values, posing a challenge to traditional political patterns. As the influence of these movements grows, Italy's political future remains tied to their ability to fulfill their electoral promises and their role in reshaping Italian identity in the face of local, regional, and international challenges..